2019
DOI: 10.25299/perspektif.2019.vol10(2).3991
|View full text |Cite
|
Sign up to set email alerts
|

Profil Kesulitan Bertanya Pada Proses Pembelajaran Perkembangan Hewan Mahasiswa Pendidikan Biologi Universitas Islam Riau Pekanbaru

Abstract: This study aims to determined factors of questioning difficulty during learning process on Animal Development study. The type of study was survey, using questionnaire, interview, and documentation as study’s instrument. The population subject of this study was third semester student of Biology Education with total 70 students. Analysis method was using descriptive method. As the result of the study shown that questioning difficulty was affected by internal factor 56,21% categorized as adequately and affected b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
2
0
3
Order By: Relevance
“…Salinity and temperature parameters were suspected to be essential for juvenile crabs, thus making the energy obtained from feed less for metabolic processes and more for growth. Following the statement of [1], the development of crab larvae from the zoea stage to the juvenile stage requires a salinity between 26-32 ppt. Low and high salinity ranges can cause test crabs to be stressed.…”
Section: Absolute Growth Of Carapace Widthmentioning
confidence: 99%
“…Salinity and temperature parameters were suspected to be essential for juvenile crabs, thus making the energy obtained from feed less for metabolic processes and more for growth. Following the statement of [1], the development of crab larvae from the zoea stage to the juvenile stage requires a salinity between 26-32 ppt. Low and high salinity ranges can cause test crabs to be stressed.…”
Section: Absolute Growth Of Carapace Widthmentioning
confidence: 99%
“…Students' low questioning skills at first can be caused by various factors. Several studies have shown that the factors causing low student questioning skills are low student self-confidence (Ginanjar et al, 2019), low interest in the material (Suryanti et al, 2019), low understanding of concepts (Muslichatun et al, 2021), method learning applied by the teacher (Hendawati & Kurniati, 2020), the attitude and nature of the teacher (Jais et al, 2019). According to Hasibuan (2009), asking is a verbal utterance that asks for a response from someone who is subjected to it.…”
Section: Hypothesis Testingmentioning
confidence: 99%
“…Keterampilan bertanya siswa yang rendah tersebut disebabkan oleh berbagai faktor. Beberapa penelitian menunjukkan bahwa faktor penyebab rendahnya keterampilan bertanya siswa adalah rasa percaya diri siswa rendah (Ginanjar et al, 2019), ketertarikan dengan materi rendah (Suryanti et al, 2019), pemahaman konsep rendah (Muslichatun et al, 2021), metode pembelajaran yang diterapkan guru (Hendawati & Kurniati, 2020), sikap dan pembawaan guru (Jais et al, 2019), serta respon teman (Prilanita & Sukirno, 2017).…”
Section: Pendahuluanunclassified
“…Hasil tersebut relevan dengan penelitian Pratiwi (2019) yaitu pertanyaan siswa SMP Negeri 2 Jember termasuk dalam level kognitif rendah karena meliputi C1 dan C2 (Ika Pratiwi et al, 2019). Penyebab kualitas pertanyaan siswa yang masih rendah menurut penelitian sebelumnya antara lain ketertarikan dengan materi rendah (Suryanti et al, 2019) serta pemahaman konsep rendah (Muslichatun et al, 2021).…”
Section: "Suka Karena Dari Dulu Saya Kecil Saya Sering Sekali Membaca...unclassified
See 1 more Smart Citation